2020
DOI: 10.3390/ani10112003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Staff Working Practices in UK Horseracing

Abstract: Due to COVID-19, horseracing was required to cease all activity in March 2020; however, little is known about the pandemic’s impact on staff working practices. This study investigated the impact of COVID-19 on staff working practices during the initial lockdown phases. An online survey about working conditions during lockdown was answered by 287 participants. Chi-squared tests for independence and binary logistic regression (BLR) analysis was undertaken. A total of 53.7% (n = 154) of staff were working during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Pandemic restrictions also affected other kept animal species such as domestic equines, altering working practices, interactions and access to equine care ( Davies et al, 2020 ). A survey undertaken in the UK reported that “ the financial impact of the pandemic combined with restricted access to veterinary professionals resulted in owners expressing concerns that horse health and welfare may be compromised as a result.…”
Section: Resultsmentioning
confidence: 99%
“…Pandemic restrictions also affected other kept animal species such as domestic equines, altering working practices, interactions and access to equine care ( Davies et al, 2020 ). A survey undertaken in the UK reported that “ the financial impact of the pandemic combined with restricted access to veterinary professionals resulted in owners expressing concerns that horse health and welfare may be compromised as a result.…”
Section: Resultsmentioning
confidence: 99%
“…Care should be taken when considering working hours in relation to job demand in this study, as data collection took place during the 3rd national coronavirus lockdown between January and February 2021 [ 52 ]. Whilst many industries were closed during this period due to government-imposed restrictions, previous research from the 1st national lockdown in March 2020 shows that most horseracing staff were likely to be working the same number of hours, with only 32.8% working fewer hours during a COVID-19 lockdown than normal [ 34 ]. This suggests that the working behaviours reported in this study are representative of typical occupational demands for horseracing staff.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than being dismissed by being “furloughed”, they were kept on payroll [ 11 ]. Racehorse trainers, for instance, were able to furlough staff, introducing different working practices within yards to mitigate the effect of a smaller workforce [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%